Determinants Of Adequate Antenatal Care (Anc K6) In Indonesia - Dewi Hestiani K; Andi Tenriola; Andi Sulfikar; Fardi Fardi (Indonesian Journal of Nursing and Health Care, 2026)
Background: Adequate antenatal care (ANC) is essential for reducing maternal and neonatal morbidity and mortality. Despite high initial ANC contact coverage in Indonesia, fulfillment of the six-visit standard (ANC K6) remains limited and socially patterned.Objective: This study aimed to describe sociodemographic and socioeconomic determinants associated with adequate antenatal care (ANC K6) in Indonesia using national survey data.Methods: A cross-sectional descriptive analysis was conducted using aggregated data from the 2023 Indonesian Health Survey, including 70,916 women aged 10–54 years who had given birth. The outcome variable was fulfillment of ANC K6. Independent variables included maternal age, education, marital status, parity, place of residence, and household wealth quintile. The analysis examined distributional patterns of ANC K6 across determinant categories without inferential modeling.Results: Nationally, only 17.6% of mothers fulfilled the ANC K6 standard. Among mothers who achieved ANC K6, the majority were aged 20–34 years (76.5%), had secondary or higher education (79.3%), resided in urban areas (57.6%), and belonged to higher wealth quintiles (49.7%). These findings indicate a pronounced social gradient in continuity of antenatal care utilization.Conclusion: Adequate antenatal care in Indonesia remains low and unequally distributed. Structural factors including education, residence, and household wealth - appear to shape continuity of care. Policies should prioritize reducing barriers to repeated visits among socioeconomically disadvantaged populations.